Institutions for irrigation management in farmer-managed systems: examples from the hills of Nepal - Martin, E.D.; Yoder, R. (International Irrigation Management Institute, 1987)
The paper examines farmer organizations and property rights which have evolved as institutions in Nepal that enable collective management of water for agricultural production.